2002
DOI: 10.1159/000063835
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Blocks in Stereotactic Neurosurgery

Abstract: The advantage of performing preoperative nerve blocks of the supraorbital and occipital nerves facilitates frame fixation and the perioperative management of patients in stereotactic neurosurgery, resulting in better patient handling with reduced intraoperative medication and less monitoring by anesthesia personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Patients in the SB group required significantly less antihypertensive medication with an overall more stable BP profile over time. This phenomenon could also be found comparing SB and LA or saline for craniotomy under GA. 21 In another study, patients without SB needed significantly deeper anesthesia to maintain normal BP and HR during craniotomy under GA. 6 Both a single asymptomatic cortical ICH and a symptomatic ICH of the internal capsule occurred in the LA group in the present series. The patient with capsular ICH became symptomatic during surgery, whereas the cortical ICH was an incidental finding in the postoperative CT scan.…”
Section: Effect Of Scalp Block On Blood Pressure and Risk Of Hemorrhagementioning
confidence: 98%
“…Patients in the SB group required significantly less antihypertensive medication with an overall more stable BP profile over time. This phenomenon could also be found comparing SB and LA or saline for craniotomy under GA. 21 In another study, patients without SB needed significantly deeper anesthesia to maintain normal BP and HR during craniotomy under GA. 6 Both a single asymptomatic cortical ICH and a symptomatic ICH of the internal capsule occurred in the LA group in the present series. The patient with capsular ICH became symptomatic during surgery, whereas the cortical ICH was an incidental finding in the postoperative CT scan.…”
Section: Effect Of Scalp Block On Blood Pressure and Risk Of Hemorrhagementioning
confidence: 98%
“…Having anesthesia in the magnetic resonance (MR) environment usually prolongs the procedure. It has been demonstrated that two occipital (n. occipitalis major and minor) as well as supraorbital blocks before starting the procedure are advantageous [78]. If necessary, additional local anesthetics can be applied around the pins of the frame (mixture of short and long acting local anesthetic).…”
Section: Operative Techniquementioning
confidence: 99%